2005
DOI: 10.2166/wst.2005.0166
|View full text |Cite
|
Sign up to set email alerts
|

Model uncertainty – parameter uncertainty versus conceptual models

Abstract: Uncertainties in model structures have been recognised often to be the main source of uncertainty in predictive model simulations. Despite this knowledge, uncertainty studies are traditionally limited to a single deterministic model and the uncertainty addressed by a parameter uncertainty study. The extent to which a parameter uncertainty study may encompass model structure errors in a groundwater model is studied in a case study. Three groundwater models were constructed on the basis of three different hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 10 publications
3
83
1
Order By: Relevance
“…Harrar et al (2003) and Højberg and Refsgaard (2005) present two different examples, both using three different conceptual models, based on three alternative geological interpretations for multi-aquifer system representative of eastern part of Denmark with glacial till plains (Højberg and Refsgaard, 2005) and in sandy outwash plains in the western part of Denmark (Harrar et al, 2003). Each of the models was calibrated against piezometrical head data using inverse optimisation.…”
Section: What Is a Hydrogeological Conceptual Model?mentioning
confidence: 99%
See 2 more Smart Citations
“…Harrar et al (2003) and Højberg and Refsgaard (2005) present two different examples, both using three different conceptual models, based on three alternative geological interpretations for multi-aquifer system representative of eastern part of Denmark with glacial till plains (Højberg and Refsgaard, 2005) and in sandy outwash plains in the western part of Denmark (Harrar et al, 2003). Each of the models was calibrated against piezometrical head data using inverse optimisation.…”
Section: What Is a Hydrogeological Conceptual Model?mentioning
confidence: 99%
“…However, when the models were used to extrapolate beyond the calibration data for predictions of solute transport and travel times the three models differed dramatically. When assessing the uncertainty contributed by the model parameter values using Monte Carlo simulations, the overlap of uncertainty ranges between the three models by Højberg and Refsgaard (2005) significantly decreased when moving from groundwater heads to capture zones and travel times. The larger the degree of extrapolation, the more the underlying conceptual model dominates over the parameter uncertainty and the effect of calibration.…”
Section: What Is a Hydrogeological Conceptual Model?mentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual uncertainty is a well described phenomenon [Beven, 2009;Konikow and Bredehoeft, 1992;Refsgaard et al, 2006;Walker et al, 2003], which is often found to be a major source of uncertainty and must therefore be considered [Bredehoeft, 2005;Harrar et al, 2007;Højberg and Refsgaard, 2005;Troldborg et al, 2007]. The challenge of quantifying conceptual uncertainty has been discussed in the literature and many methods have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to alleged correct results, for instance when addressing the water balance on catchment scale, but will often prove to be inadequate for simulations beyond general flows and heads, e.g., contaminant transport modeling. Therefore, it is proposed by numerous studies that the uncertainty on the geological conceptualization is crucial when assessing uncertainties on flow paths (Neuman, 2003;Bredehoeft, 2005;Hojberg and Refsgaard, 2005;Troldborg et al, 2007;Seifert et al, 2008). One of the strategies often recommended for characterizing geological uncertainty and assessing its impact on hydrological predictive uncertainty is the use of multiple geological models (Renard, 2007;Refsgaard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%